Kendala Pengembangan Wisata Watu Joli Desa Pucung Kidul, Kecamatan Boyolangu, Tulungagung - Febrianti, Sakina Duwita; Aslama, Ade; Putranto, Anggoro (Program Studi Pariwisata Program Sarjana, Fakultas Pariwisata, Universitas Udayana, 2023)
Watu Jolì Tourism is one of the tourist attractions located in Tulungagung Regency, East Java, Indonesia. Tourism Watu Joli Tulungagung may have great potential, but there are several obstacles encountered in its development. The purpose of this study is to examine the obstacles to tourism development at Watu Joli Tulungagung. This study uses descriptive qualitative methods through interviews with managers, observations, and retrieves information from relevant literature sources. The results of the study show that the obstacles in the development of Watu Joli tourism include budget constraints, environmental problems, lack of participation from stakeholders, and lack of tourism promotion. To overcome these obstacles, various efforts need to be made, such as finding adequate sources of funds, better environmental management, increasing stakeholder participation, and increasing promotion of Watu Joli. Keywords: Constraints, Tourism Development, Watu Jol